Extended Spectrum Beta-lactamase producing Salmonella Lindenberg gastroenteritis - Prabhurajan, Rajan; Kiran, Rajasekharapanicker; Padmavathy, Kesavaram (The Journal of Infection in Developing Countries, 2019)
Introduction: Increasing antimicrobial resistance among non-typhoidal Salmonella (NTS) is a major public health issue especially in developing countries and is partly due to the use of antimicrobials in animal feeds as growth promoters. NTS are often associated with self-limiting acute gastroenteritis (AGE). Nevertheless, fluoroquinolones and third-generation cephalosporins are currently used in the treatment of severe diarrhoeal infections. Methodology: We report the case of a 30-year-old male who presented with clinical symptoms of moderate gastroenteritis. Stool culture and antibiotic susceptibility was performed as per standard microbiological methods. Molecular detection of bla genes was carried out by PCR. Results: The isolate was confirmed as S. Lindenberg by serotyping. The isolate exhibited dual resistance to fluoroquinolone and third generation cephalosporins. The isolate was an ESBL producer and harboured blaSHV. Based on the antibiotic susceptibility pattern, the patient was successfully treated with ceftriaxone-tazobactam. Conclusion: Presently, there are no Indian reports on the blaSHV positive ESBL producing S. Lindenberg gastroenteritis. We report on the successful management of the first case of acute gastroenteritis caused by S. Lindenberg that exhibited dual resistance to fluoroquinolone and third generation cephalosporins. Continued surveillance of the antibiotic resistance pattern of the Non-typhoidal Salmonella serovars circulating in the geographical region is warranted.